Watch and Learn Rhetorical Devices in Classroom Films after 1940 - Masson, Eef (Framing Film, 2012)
Since the late 1990s, there has been a marked increase in academic interest in what are sometimes called 'utility films', intended for purposes of information, training, teaching or advertising. Although such research was long overdue, the current academic output tends to be restricted in scope, paying little attention to the films' textual features: the means they deploy in defending their informational, educational or commercial arguments. In the absence of such studies, the image survives of very 'formulaic' genres. This book seeks to modify this picture, and suggests a methodology that helps to foreground the films' rhetorical diversity. Taking her departure from a historic collection of Dutch classroom films, Masson proposes an approach that considers an audio-visual text as part of a so-called dispositif: the set-up of technology, text and viewing situation that is relevant to the specific corpus under scrutiny.